Students' Learning Motivation in Distance Learning During the COVID- 19 Pandemic Period at Primary School - Veronika, Veronika; Setiawan, Wawan; Fazriyah, Nurul (International Conference on Elementary Education, 2021)
In the Corona Virus Disease (COVID-19) pandemic situation teaching and learning activities are carried out by distance learning / online learning. This study aims to explain the learning motivation of students in participating in distance learning during the COVID-19 pandemic. This study involved 31 students of grade V one of the elementary schools in Bandung. This study uses a quantitative approach with a survey method using 25 statement items with a Likert scale that have been validated by experts using google form so that students can easily access it. The data processing technique used in this study was to calculate the percentage of data and an analysis was carried out on each indicator, namely indicators of self-desire, self-worth, concentration, enthusiasm, advice, and punishment. The results of this study indicate that the learning motivation of students during the COVID-19 pandemic shows a percentage of 70.3% with good criteria. Based on these results, it can be stated that learning in elementary schools during the COVID-19 epidemic can run well through a distance learning approach.